The feasibility of crop insurance agency acquisitions - Davis, Bill (Kansas State University, 2012)
Crop insurance, in recent years, has displaced U.S. federal farm program payments as the most important safety net for net farm income. The business climate that crop insurance purchasers and providers face in the future is one of increasing premiums for producers and decreasing commissions for crop insurance companies and agents. The primary objective of this thesis is to assess the desirability of crop insurance agency acquisitions to increase market share for Farm Credit Services of America, considering the significant uncertainties in the future subsidy levels and commission levels for these products. Financial analysis and modeling crop insurance agency acquisitions is completed under a wide range of future economic and political scenarios. The wide range of assumptions, however, does contribute to a wide range of potential purchase prices and rates of return on crop insurance agency acquisitions. The crop insurance industry faces uncertainty in the future and general industry profitability will likely decline. However, an expansion strategy in a period of reduced commissions can be profitable if acquisitions are priced appropriately and can be made in locations where existing support services can be leveraged to support the acquisition.
Keywords: Crop insurance; Acquisitions; Net present value; Farm credit; Feasibility analysis; Agricultural policy; Agriculture, General (0473); Economics, Agricultural (0503); Economics, Finance (0508)